General dermatology and dermatology in primary healthcare - Vibhaan Mathur; Adam Daunton; Gia T Tang (Clinical and Experimental Dermatology, 2026)
A six-month-old infant presented with persistent scabies symptoms despite appropriate permethrin treatment and environmental decontamination measures. While permethrin resistance was considered, the case highlights the importance of recognising asymptomatic familial carriage and pseudoresistance as more likely causes of treatment failure in classic scabies.